2019
DOI: 10.1097/jxx.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Practice patterns of nurse practitioners related to weight management in primary care

Abstract: Background and objectives: Obesity prevalence rates for adults are at an all-time high. This systematic review of the literature aimed to examine the practice patterns of nurse practitioners (NPs) related to weight management in primary care and recommend future areas of research as it relates to the diagnosis and management of patients with obesity by NPs. Data sources: The databases CINAHL PLUS with Full Text, Cochrane Central Register of Controlled T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Education-Provider included five studies [ 31 , 32 , 64 , 69 , 70 ]. Provider knowledge was assessed for the use of the Australasian Triage Scale, patient counselling on obesity, skin cancer detection and training, early detection of skin cancer, and orientation in long-term care.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Education-Provider included five studies [ 31 , 32 , 64 , 69 , 70 ]. Provider knowledge was assessed for the use of the Australasian Triage Scale, patient counselling on obesity, skin cancer detection and training, early detection of skin cancer, and orientation in long-term care.…”
Section: Resultsmentioning
confidence: 99%
“…Interprofessional Team Functioning was examined in four reviews [ 32 , 44 , 52 , 69 ]. Providers expressed positive perceptions of high functioning interprofessional teams [ 69 ] and improved communication (McParland, 2022) (no p value reported) [ 52 ]. In their review on long-term care, Lovink et al stated that no provider outcomes were identified [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations